Recommendations on Fecal Immunochemical Testing to Screen for Colorectal Neoplasia: A Consensus Statement by the US Multi‐Society Task Force on Colorectal Cancer. (January 2017) - Robertson, Douglas J; Lee, Jeffrey K; Boland, Richard C; Dominitz, Jason A; Giardiello, Francis M; Johnson, David A; Kaltenbach, Tonya; Lieberman, David; Levin, Theodore R; Rex, Douglas K
Abstract : N/A: The use of the fecal occult blood test (FOBT) for colorectal cancer (CRC) screening is supported by randomized trials demonstrating effectiveness in cancer prevention and widely recommended by guidelines for this purpose. The fecal immunochemical test (FIT), as a direct measure of human hemoglobin in stool has a number of advantages relative to conventional FOBT and is increasingly used relative to that test. This review summarizes current evidence for FIT in colorectal neoplasia detection and the comparative effectiveness of FIT relative to other commonly used CRC screening modalities. Based on evidence, guidance statements on FIT application were developed and quality metrics for program implementation proposed.